A framework for prescription in exercise‐oncology research†. Issue 2 (11th May 2015) - Sasso, John P.; Eves, Neil D.; Christensen, Jesper F.; Koelwyn, Graeme J.; Scott, Jessica; Jones, Lee W.
Abstract: The field of exercise‐oncology has increased dramatically over the past two decades, with close to 100 published studies investigating the efficacy of structured exercise training interventions in patients with cancer. Of interest, despite considerable differences in study population and primary study end point, the vast majority of studies have tested the efficacy of an exercise prescription that adhered to traditional guidelines consisting of either supervised or home‐based endurance (aerobic) training or endurance training combined with resistance training, prescribed at a moderate intensity (50–75% of a predetermined physiological parameter, typically age‐predicted heart rate maximum or reserve), for two to three sessions per week, for 10 to 60 min per exercise session, for 12 to 15 weeks. The use of generic exercise prescriptions may, however, be masking the full therapeutic potential of exercise treatment in the oncology setting. Against this background, this opinion paper provides an overview of the fundamental tenets of human exercise physiology known as the principles of training, with specific application of these principles in the design and conduct of clinical trials in exercise‐oncology research. We contend that the application of these guidelines will ensure continued progress in the field while optimizing the safety and efficacy of exercise treatment following a cancer diagnosis.